Active Cancellation of the Tonal Component of Sound Using a Discrete Fourier Transform of Variable Length - ŁUCZYNSKI, Michał; DOBRUCKI, Andrzej; BRACHMAŃSKI, Stefan (Archives of Acoustics, 2021)
The paper presents a method of eliminating the tonal component of an acoustic signal. The tonal component is approximated by a sinusoidal signal of a given amplitude and frequency. As the parameters of this component: amplitude, frequency and initial phase may be variable, it is important to detect these parameters in subsequent analysis time intervals (frames). If the detection of the parameters is correct, the elimination consists in adding a sinusoidal component with the detected amplitude and frequency to the signal, but the phase shifted by 180 degrees. The accuracy of the reduction depends on the accuracy of parameters detection and their changes.Detection takes place using the Discrete Fourier Transform, whose length is changed to match the spectrum resolution to the signal frequency. The operation for various methods of synthesis of the compensating signal as well as various window functions were checked. An elimination simulation was performed to analyze the effectiveness of the reduction. The result of the paper is the assessment of the method in narrowband active noise control systems. The method was tested by simulation and then experimentally with real acoustic signals. The level of reduction was from 6.9 to 31.5 dB.